Analisis Kinerja Karyawan PT Cahaya Tirta Rasa Menggunakan Metode 360 Degree Feedback : Employee Performance Analysis at PT Cahaya Tirta Rasa Using the 360 Degree Feedback Method - Sely Veronica; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the performance of employees at PT. Cahaya Tirta Rasa using the 360 Degree Feedback method. In the beverage sector, it plays an important role in the Indonesian economy. The 360 Degree Feedback method involves feedback from evaluations at various levels within the company as well as from external sources; this method involves people around the evaluated employees. This research uses a qualitative method by collecting responses through surveys and interviews with a primary focus on the performance of administrative staff. The study covers assessments of work quality, work speed, and technical competence. It involves 4 administrative staff members from PT. Cahaya Tirta Rasa during the period from May 2025 to July 2025. The results show that the administrative staff's work quality reaches 90%. The average time to complete tasks is 57.2 hours, and technical competence of 8.92. This study concludes that the application of the 360 Degree Feedback Method in evaluating employee performance provides feedback such as increased training for Admin and the creation of open green spaces for employees to minimize burnout. This research is expected to contribute to the development of performance within the company.